Hydrogen peroxide and water availability effect on vegetative growth of soybean [Glycine max (L.) Merr.] Variety Deja 1 - Enita Simbolon; Sri Widodo Agung Suedy; Sri Darmanti (Agric, 2020)
Soybean plant [Glycine max (L.) Merr.] Is a food crop that is a source of fat, protein, and minerals. Drought stress is a major obstacle in the cultivation of soybean plants, which causes the synthesis of excessive amounts of Reactive Oxygen Species (ROS) which triggers oxidative stress. Hydrogen peroxide (H2O2) is the most stable ROS, in low concentrations it can act as a signaling molecule and activate an antioxidant defense system to protect plants from oxidative stress. The study was conducted at the Plant Structure and Function Biology Laboratory of Diponegoro University. The study aims to determine the effect of H2O2 treatment on the condition of different levels of water availability on the vegetative growth of soybean plants variety Deja 1. Research using a completely randomized design (CRD) 4x2 factorial pattern. The first factor is H2O2 concentration (0 0.5 1 and 2 mM). The second factor is the level of water availability (100 and 35% of field capacity). Each treatment was repeated 5 times. Quantitative data were analyzed by Analysis of Variance (ANOVA) followed by DMRT test at 95% confidence level. The results showed that there was an interaction between the H2O2 concentration factor and the level of water supply to the canopy fresh weight. The 2 mM H2O2 treatment at 100% water availability and 1 mM H2O2 with 35% water availability increased vegetative growth as indicated by the canopy and root fresh weight parameters, number of leaves, stomata opening width, relative water content. Based on the results of the study it can be stated that the exogenous H2O2 treatment of leaves with certain concentrations at all different levels of water availability can increase the vegetatif growth of soybean variety of Deja 1.